A constraint programming approach for the premarshalling problem - Jiménez-Piqueras, Celia; Ruiz, Rubén; Parreño-Torres, Consuelo; Alvarez-Valdes, Ramon (European journal of operational research, 2023)
•We address the container premarshalling problem, CPMP.•A series of constraint programming models to optimally solve the CPMP is proposed.•Constraint programming differs in model construction logic from mathematical models.•We evaluate the performance of our proposal with an extensive computational study. The enormous amount of containers handled at ports hampers the efficiency of terminal operations. The optimization of crane movements is crucial for speeding up the loading and unloading of vessels. To this end, the premarshalling problem aims to reorder a set of containers placed in adjacent stacks with a minimum number of crane movements, so that a container with an earlier retrieval time is not below one with a later retrieval time. In this study, we present a series of constraint programming models to optimally solve the premarshalling problem. Extensive computational comparisons show that the best proposed constraint programming formulation yields better results than the state-of-the-art integer programming approach. A salient finding in this paper is that the logic behind the model construction in constraint programming is radically different from that of more traditional mixed integer linear programming models.